Rancang Bangun Boiler Pemanas Tahu Kapasitas 90 kW Dengan Tungku Gasifikasi Berbahan Bakar Sekam Padi - Ahmad Maulana Kartika; Aa Setiawan; Dedi Suwandi; Wardika Wardika (JURNAL MECHANICAL, 2017)
Boilers that used in the tofu industry in Indramayu are still use firewood as a fuel. The use of firewood as a fuel in boiler is not effective because it affects the destruction of forests as producers of plants (timber) and oxygen in earth. On the other hand there are also many rice husks that mount in the rice mill and has not been utilized by the surrounding community. Therefore, this research is conducted to utilize rice husk as fuel in boiler for cooking tofu with boiler. This research begins by doing a survey in the field of industry to know about the capacity of traditional wood-fired boilers, which capacity is obtained of 90kW capacity. Then the next step is making boiler husk based on the existing calculations to determine the size of the boiler to be made. Data retrieval is carried out until the temperature of the air boils with a tolerance of up to 30 minutes. Based on the results of the test, the rice husk boiler that has a capacity of 98.3 kW, greater than the value of designing that only 90 kW capacity of combustion and able to heat 190 kg of water within 35 minutes, so it can be used as a substitute of firewood boiler.